Preschool Literacy The Effect of Sociocultural Context - Quintero, Elizabeth ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
A study investigated the literacy development of bilingual children as they interacted in the social context of their preschool classrooms. Subjects were 12 native Spanish speaking preschoolers in a headstart classroom. It was hypothesized that what bilingual children bring to the classroom in terms of experience, values, language, culture, and personality affects the social context of the classroom and, in turn, affects the developmental process of the children's literacy acquisition. Because literacy was being investigated as a holistic process consisting of many components and many different behaviors, ethnographic techniques were used to observe and analyze the children's interaction approximately 100 hours in a five month period. Results indicated that the children overwhelmingly preferred group activity and play with others as opposed to being alone. Preschool children used the various literacy behaviors often in the social context of the classroom, and often for the purpose of interaction. Almost all subjects chose to use language as their main vehicle for social interaction. Among the conclusions based on these results are that cultural traits and customs can affect preschoolers' learning environment in positive ways, and that children are influenced by role models in all aspects of literacy development. It was recommended that preschool programs should provide bilingual programs that emphasize (1) language interaction, (2) content and activities based on cultural values, (3) developmentally appropriate writing tasks, (4) daily opportunities for literacy development, (5) role models, and (6) parent and teacher training in developing and integrating literacy skills. (Several examples of children's art work are included. Graphs depicting semiotic literacy behaviors used for social interaction and resulting active learning are appended. Six references are included.) (JD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education; Classroom Environment; Cognitive Development; Cultural Influences; Emergent Literacy; English (Second Language); Ethnography; Intercultural Communication; Language Acquisition; Learning Processes; Peer Relationship; Preschool Education; Reading Research; Social Attitudes; Social Influences; Spanish Americans; Spanish Culture; Spanish Speaking; Early Writing; Reports, Research